THE PROSPECTS OF THE RUSSIAN-CHINESE HUMANITARIAN COOPERATION IN FRAMEWORK OF "ONE BELT, ONE ROAD" INITIATIVE IMPLEMENTATION - D. A. Smaliakou (Russian State Vocational Pedagogical University, 2018)
Introduction. Nowadays, the steadily growing relationship with the People's Republic of China is one of the priority directions of the foreign policy of the Russian Federation. According to the author of the present paper, new opportunities for active constructive interaction between the countries are provided with the One Belt and One Road Initiative (OBOR or BRI) adopted by China for the purpose of combination of efforts of the states for stable development of economy in the Eurasian space and peaceful co-existence of the people on the basis of the principles of openness, inclusivity of different civilizations, tolerance, safety, mutual benefit and training.The aim of the paper is to discuss the status and prospects of the RussianChinese cooperation in the humanitarian field and search for new narrative for development cooperation.Methodology and research methods. The research was performed with a support on philosophical and general scientific methods: comparative, structurally functional and system types of analysis, synthesis, generalization, and forecasting.Results and scientific novelty. The Russian-Chinese recent cooperation was considered. Special attention was given to education communication strategy as one of the reliable and checked channels of establishment and consolidation of international economic relations. The educational component of humanitarian interaction enables to provide effective tools for adjustment and support for the international dialogue and has an extensive range of opportunities for harmonization of cultural, social and even political standards.It is emphasized that further strengthening of the productive bilateral interaction of the People's Republic of China and the Russian Federation is prevented by its developed model which is under construction and functions mainly at the level of public authorities. In spite of the fact that the relations between two countries are on the rise, the potential of the existing model has become exhausted, and it is therefore necessary to search for other ways of future joint collaborative work. Strengthening of partnership requires the transition to multilateral cooperation with other states and mutual participation of Russia and China in the course of overcoming the social and economic imbalance in the zone of their shared interests - the territory of the revived Silk Road. The third countries located along its southern transit corridor, unlike the states of the northern direction, are characterized by the backwardness of economics, high unemployment rate, lack of the fair system of upward mobility, poverty and ignorance of the population, thus promoting the spread of religious extremism and escalation of international conflicts. The author proposed to involve the humanitarian sphere as the mechanism of the start of transcontinental infrastructure projects in order to normalize the social and economic situation in these regions, to overcome socio-cultural barriers and to achieve integration of economics of various states for the sake of their steady growth and effectivization. The coordinated actions of China, Russia and EU countries for the promotion and maintenance of modern models of education can become a decisive factor to stabilize and implement the One Belt and One Road Initiative in problematic regions. In the author's view, partner States should focus on actions for modernization of national education systems and dissemination of scientific worldview, e.g. in the regions of the Northern Silk Road. Otherwise, the South will remain the centre of regularly military conflicts and terrorism financing, whereas the Russian and Chinese companies will continue to spend considerable personnel and financial resources for the safety of the ongoing joint projects.Practical significance. Materials of the research can be useful as a guide to reconsider the objectives of the Russian-Chinese alliance in the humanitarian sphere and generate new ideas on development and ways of implementation of the international educational programs.